Comparative study of therapeutic effect between scapular stabilized and general exercise in the fourth year’s dental students, Faculty of Dentistry, KhonKaen University - Muanchat, Tanaphong; Sae-Lee, Daraporn; Bumrerraj, Sauwanan; Paungmali, Aatit; Mator, Lugkana; Wanpen, Sawitri; Boonprakob, Yodchai (Journal of Associated Medical Sciences, 2017)
Background: Poor posture is a common cause for neck pain, back pain, and low back pain. Working position of some careers lead to these disorders. For example, dentists always work in forward head posture and shoulder abduction. Thus, a good posture with working position and exercise are procedures for prevention and treatment simultaneously. Objectives: To compare the effectiveness between scapular stabilized and general exercise on alteration of craniovertibral angle, ability of utilizing of craniocervical flexor muscles, and strength of scapular muscles (serratus anterior, middle trapezius, lower trapezius, and rhomboid muscles) of the 4th year’s dental students. Materials and methods: A quasi-experimental study was designed for this current study. Seventy four participants of the 4th year’s dental studentswere recruited and divided randomly into two groups by sections ofstudying. Thirty seven participants were performed scapular stabilized exercise (group 1) and thirty seven participants were performed general exercise (group2), respectively. These exercises were inserted during clinical practice period which were performed 15 minutes per time, 2 times per day, and once a week in 3 months. All of measurements were tested before exercise, one month after exercise, and three months after exercise. Results: 1) Means of CV angle before exercise, one month after exercise, and three monthsafter exercise of group 1 were 50.55±5.14, 52.04±2.94, and 53.64±2.94 degrees. For group 2, the means of CV angle were 52.04±2.94, 51.99±3.00, and 54.59±3.00 degrees. 2) Means of ability of utilizing of neck flexor muscles were increased significantly in both groups. 3) Means of scapular muscles wereincreased significantly in both groups. Conclusion: Scapular stabilized exercise and general exercise can increase ability of utilizing of neck flexor muscles and increase strength of scapular muscles similarly. However, scapular stabilized exercise showed improvement of CV angle faster than general exercise.